Survival, growth, and biogenic amine production of Enterococcus faecium FC12 in response to extracts and essential oils of Rubus fruticosus and Juniperus oxycedrus - Montanari, Chiara; Barbieri, Federica; Lorenzini, Silvia; Gottardi, Davide; Šimat, Vida; Özogul, Fatih; Gardini, Fausto; Tabanelli, Giulia (Frontiers in Nutrition, 2023)
Enterococci are lactic acid bacteria (LAB) usually found as food contaminants in fermented products such as cheeses and fermented sausages. Due to their antibiotic resistance, presence of virulence factors and ability to produce biogenic amines (BAs), the determination of these bacteria is crucial to assure food quality and safety. BAs production and consequent accumulation in foods can cause toxicological effects on human health. Plant phenolic compounds are promising alternatives to chemical preservatives and reflect the consumers’ demand for “green” solutions. In this study, the antimicrobial effect of blackberry (Rubus fruticosus) leaves and prickly juniper (Juniperus oxycedrus) needles both as phenolic extracts (PE) and essential oils (EO), were evaluated against Enterococcus faecium FC12, a known tyramine-producing strain. The growth kinetics in presence of sub-lethal concentrations of such plant derivatives were modeled and BA production was monitored over time. Moreover, flow cytometry (FCM) was used to study the effects of EOs and PEs on cell viability. The EOs showed a higher antimicrobial effect (especially R. fruticosus added at 0.75 mg/ml), determining an initial decrease of culturable cells followed by a recovery, even if with lower growth rates and final cell loads. Different rates of BA formation were observed, with tyramine concentrations ranging from 120 to 160 mg/l after 96 h of incubation, and 2-phenylethylamine produced in lower amounts, usually after reaching the peak of tyramine. FCM confirmed the higher efficacy of R. fruticosus EO that induced cell membrane injury in 93% of the total population. However, a complete recovery occurred in the following incubation demonstrating a transient damage. Although further research is required to better investigate this recovery and to assess the suitability of this approach in a real food system, the present study showed the potential antimicrobial activity of plant derivatives, especially R. fruticosus EO, against the tyramine-producing E. faecium FC12.